Sucking or lapping: facultative feeding mechanisms in honeybees (Apis mellifera) - Wei, Jiangkun (Biol Lett, 2020)
Nectarivorous insects generally adopt suction or lapping to extract nectar from flowers and it is believed that each species exhibits one specific feeding pattern. In recent literature, large groups of nectarivores are classified as either ‘suction feeders', imbibing nectar through their proboscis, or ‘lappers', using viscous dipping. Honeybees (Apis mellifera) are the well-known lappers by virtue of their hairy tongues. Surprisingly, we found that honeybees also employ active suction when feeding on nectar with low viscosity, defying their classification as lappers. Further experiments showed that suction yielded higher uptake rates when ingesting low-concentration nectar, while lapping resulted in faster uptake when ingesting nectar with higher sugar content. We found that the optimal concentration of suction mode in honeybees coincided with the one calculated for other typical suction feeders. Moreover, we found behavioural flexibility in the drinking mode: a bee is able to switch between lapping and suction when offered different nectar concentrations. Such volitional switching in bees can enhance their feeding capabilities, allowing them to efficiently exploit the variety of concentrations presented in floral nectars, enhancing their adaptability to a wide range of energy sources.